Synaptic vesicle release during ribbon synapse formation of cone photoreceptors - Davison, Adam; Gierke, Kaspar; Brandstätter, Johann Helmut; Babai, Norbert (Frontiers in Cellular Neuroscience, 2022)
Mammalian cone photoreceptors enable through their sophisticated synapse the high-fidelity transfer of visual information to second-order neurons in the retina. The synapse contains a proteinaceous organelle, called the synaptic ribbon, which tethers synaptic vesicles (SVs) at the active zone (AZ) close to voltage-gated Ca2+ channels. However, the exact contribution of the synaptic ribbon to neurotransmission is not fully understood, yet. In mice, precursors to synaptic ribbons appear within photoreceptor terminals shortly after birth as free-floating spherical structures, which progressively elongate and then attach to the AZ during the following days. Here, we took advantage of the process of synaptic ribbon maturation to study their contribution to SV release. We performed whole-cell patch-clamp recordings from cone photoreceptors at three postnatal (P) development stages (P8-9, P12-13, >P30) and measured evoked SV release, SV replenishment rate, recovery from synaptic depression, domain organization of voltage-sensitive Ca2+ channels, and Ca2+-sensitivity of exocytosis. Additionally, we performed electron microscopy to determine the density of SVs at ribbon-free and ribbon-occupied AZs. Our results suggest that ribbon attachment does not organize the voltage-sensitive Ca2+ channels into nanodomains or control SV release probability. However, ribbon attachment increases SV density at the AZ, increases the pool size of readily-releasable SVs available for evoked SV release, facilitates SV replenishment without changing the SV pool refilling time, and increases the Ca2+- sensitivity of glutamate release.